(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores a system for teaching higher mathematics to students majoring in chemistry, using adaptive and integrative approaches. Within the proposed framework, mathematical topics are introduced in a chemical context, tailored to individual learning needs, and presented through real-life examples. The article describes the main instructional stages, key principles, and pedagogical benefits of the system. The approach enhances interdisciplinary thinking, fosters independent reasoning, and strengthens students’ professional preparedness.